Low-temperature effect on enzyme activities involved in sucrose-starch partitioning in salt-stressed and salt-acclimated cotyledons of quinoa (Chenopodium quinoa Willd.) seedlings - Rosa, Mariana Daniela (2009)
The effect of low temperature on growth, sucrose-starch partitioning and related enzymes in salt-stressed and salt-acclimated cotyledons of quinoa (Chenopodium quinoa Willd.) was studied. The growth of cotyledons and growing axes in seedlings grown at 25/20 °C (light/dark) and shifted to 5/5 °C was lower than in those only growing at 25/20 °C (unstressed). However, there were no significant differences between low-temperature control and salt-treated seedlings. The higher activities of sucrose phosphate synthase (SPS, EC 2.4.1.14) and soluble acid invertase (acid INV, EC 3.2.1.25) were observed in salt-stressed cotyledons; however, the highest acid INV activity was observed in unstressed cotyledons. ADP-glucose pyrophosphorylase (ADP-GPPase, EC 2.7.7.27) was higher in unstressed cotyledons than in stressed ones. However, between 0 and 4 days the highest value was observed in salt-stressed cotyledons. The lowest value of ADP-GPPase was observed in salt-acclimated cotyledons. Low temperature also affected sucrose synthase (SuSy, EC 2.4.1.13) activity in salt-treated cotyledons. Sucrose and glucose were higher in salt-stressed cotyledons, but fructose was essentially higher in low-temperature control. Starch was higher in low-temperature control; however, the highest content was observed at 0 day in salt-acclimated cotyledons. Results demonstrated that low temperature induces different responses on sucrose-starch partitioning in salt-stressed and salt-acclimated cotyledons. Data also suggest that in salt-treated cotyledons source-sink relations (SSR) are changed in order to supply soluble sugars and proline for the osmotic adjustment. Relationships between starch formation and SuSy activity are also discussed.